The Doppler Flip in Hd 100546 as a Disk Eruption: The Elephant in the Room of Kinematic Protoplanet Searches - Carcamo-Vasquez, M; Weber, P (American Astronomical Society, 2022)
The interpretation of molecular-line data using hydrodynamical simulations of planet-disk interactions fosters new hope for the indirect detection of protoplanets. In a model-independent approach, embedded protoplanets should be found at the roots of abrupt Doppler flips in velocity centroid maps. However, the largest velocity perturbation known for an unwarped disk, in the disk of HD 100546, leads to a conspicuous Doppler flip that coincides with a thick dust ring, in contradiction with an interpretation in terms of a 31 M jup body. Here we present new ALMA observations of the 12CO(2-1) kinematics in HD 100546, with a factor of 2 finer angular resolutions. We find that the disk rotation curve is consistent with a central mass 2.1 < M ⋆/M ⊙ < 2.3 and that the blueshifted side of the Doppler flip is due to vertical motions, reminiscent of the disk wind proposed previously from blueshifted SO lines. We tentatively propose a qualitative interpretation in terms of a surface disturbance to the Keplerian flow, i.e., a disk eruption, driven by an embedded outflow launched by a 1/410 M earth body. Another interpretation involves a disk-mass-loading hot spot at the convergence of an envelope accretion streamer. © 2022. The Author(s). Published by the American Astronomical Society.